1995
DOI: 10.1016/0042-6989(95)98720-t
|View full text |Cite
|
Sign up to set email alerts
|

Attentional modulation of adaptation to two-component transparent motion

Abstract: We have studied the effects of voluntary attention on the induction of motion aftereffects (MAEs). While adapting, observers paid attention to one of two transparently displayed random dot patterns, moving concurrently in opposite directions. Selective attention was found to modulate the susceptibility to motion adaptation very substantially. To measure the strength of the induced MAEs we modulated the signal-to-noise ratio of a real motion signal in a random dot pattern that was used to balance the aftereffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
2
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(93 citation statements)
references
References 48 publications
10
80
2
1
Order By: Relevance
“…While most previous psychophysical studies have found results concordant with those reported here (Blake and Hiris 1993; Lankheet and Verstraten 1995), one study found a somewhat different result. Raymond and Braddick (1996) used test stimuli similar to our own, but only 184 ms in duration.…”
Section: Discussioncontrasting
confidence: 32%
See 1 more Smart Citation
“…While most previous psychophysical studies have found results concordant with those reported here (Blake and Hiris 1993; Lankheet and Verstraten 1995), one study found a somewhat different result. Raymond and Braddick (1996) used test stimuli similar to our own, but only 184 ms in duration.…”
Section: Discussioncontrasting
confidence: 32%
“…We used an adaptation-test paradigm similar in concept to ones used in human psychophysical studies of motion perception (Blake and Hiris 1993;Lankheet and Verstraten 1995;Raymond and Braddick 1996). The dynamic random dot stimulus we employed is similar to the ones used by Newsome and colleagues (Britten et al 1992).…”
Section: Stimulimentioning
confidence: 99%
“…Recent research has revealed an effect of attentional modulations on the detection of motion or on motion aftereffects when two components of motion overlap (e.g., Lankheet & Verstraten, 1995). Kitazaki and Sato (2003) measured the effect of voluntary attention on vection direction with a display including upward and downward optical motion.…”
Section: Discussionmentioning
confidence: 99%
“…Arman et al (2006) showed that the motion aftereffect is stronger for motion in an attended direction even when the test appears at a nonattended location, indicating enhancement of motion processing by selection of same-direction motion signals. In a similar vein, Lankheet and Verstraten (1995) elicited a motion aftereffect in a direction opposite to an attended motion layer, even when the stimulus motion was balanced by showing two clouds of dots moving in opposite directions. However, it is unclear whether feature-based attention modulates involuntary eye-movements, since recent research indicates that perception and slow eye movements rely on partially different networks or on information arising from the same networks but read out in different ways (Simoncini et al 2012;Spering and Carrasco 2012;Spering and Gegenfurtner 2007b;Spering et al 2011;Tavassoli and Ringach 2010).…”
mentioning
confidence: 99%